2023
DOI: 10.14202/vetworld.2023.1301-1311
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of phytofabricated silver nanoparticles using Carica papaya L. against Gram-negative bacteria

Mbarga Manga Joseph Arsene,
Podoprigora Irina Viktorovna,
Marukhlenko Alla
et al.

Abstract: Background and Aim: Antibiotic resistance, especially in Gram-negative bacteria, is a major public health risk affecting all industries requiring the use of antibiotics, including agriculture and animal breeding. This study aimed to use papaya extracts to synthesize silver nanoparticles (AgNPs) and evaluate their antimicrobial activity against various Gram-negative bacteria. Materials and Methods: Silver nanoparticles were synthesized from the aqueous extracts of papaya seed, root, and bark, with AgNO3 used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 48 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Findings of Zamana et al [30] demonstrated that AgNPs were more effective antibacterials than conventional rifampicin as they obtained comparatively modest inhibition zones against gram-positive and gram-negative bacteria than those achieved by conventional rifampicin. Revathi et al [31] and Arsene et al [32] found that papaya's extracts are very effective reducing agents for the biogenic production of AgNPs; later, they further explained that AgNPs that are synthesized biologically using seed and root extract exhibit notable antibacterial as well as antibiofilm capabilities [32].…”
Section: Discussionmentioning
confidence: 99%
“…Findings of Zamana et al [30] demonstrated that AgNPs were more effective antibacterials than conventional rifampicin as they obtained comparatively modest inhibition zones against gram-positive and gram-negative bacteria than those achieved by conventional rifampicin. Revathi et al [31] and Arsene et al [32] found that papaya's extracts are very effective reducing agents for the biogenic production of AgNPs; later, they further explained that AgNPs that are synthesized biologically using seed and root extract exhibit notable antibacterial as well as antibiofilm capabilities [32].…”
Section: Discussionmentioning
confidence: 99%